Toronto, the Belfast of Canada : The Orange Order and the Shaping of Municipal Culture - Smyth, William J., 1949- (Book collections on Project MUSE., 2015)
Toronto, the Belfast of Canada explores the intolerant origins of today's cosmopolitan city.